VERBAL HUMOR IN HOLOLIVE ENGLISH SELECTED CLIPS BEST OF HOLOLIVE EN - OCTOBER - Firjatullah, Muhammad Maulidya; Sunra, La; Nur, Riola Haya (ELITERATE : Journal of English Linguistics and Literature Studies, 2021)
The purpose of this study, Verbal Humor in Hololive English Selected Clips Best of Hololive EN – October, was to examine the art of verbal humor. As a first step, the researchers sought to determine what sorts of humour were used by viewers in the Best of Hololive EN - October. Another goal was to use GTVH to linguistically analyze the verbal comedy in Hololive English Selected Clips Best of Hololive EN - October. Hololive English Selected Clips Best of Hololive EN - October was used as a starting point for examining the many sorts of linguistic humor. Hololive English Selected Clips Best of Hololive EN - October linguistically analyzed verbal comedy, the second objective. The research was primarily concerned with the intricacies of human behavior. Document or content analysis was used to acquire the information needed for the investigation. Humans were the primary source of data in this study. For the first study topic, we used Shade (1996)'s verbal humour categorisation, while for the second, we used Attardo's GTVH (1994). The investigation yielded a number of discoveries. In Hololive English Selected Clips Best of Hololive EN – October, there were 21 verbal humours that fit into 9 of the 12 categories. Seven jokes were collected out of a total of 21 pieces of verbal comedy that featured inside the study's subject. After parody, pun, irony, tall tale, sarcasm, riddle, satire, and farce, the second-highest appearance was pun 4. GTVH's six Knowledge Resoures (KRS): Script Opposition, Logical Mechanism, Situation, Target (TA), Narrative Strategy (NS), and Language were used to analyze the verbal humour detected (LA). An investigation of verbal humor was carried out in a hierarchical manner, beginning with its most fundamental component.